2018
DOI: 10.1007/s00269-018-1013-7
|View full text |Cite
|
Sign up to set email alerts
|

A single-crystal neutron diffraction study of wardite, NaAl3(PO4)2(OH)4·2H2O

Abstract: The crystal structure and crystal chemistry of wardite, ideally NaAl 3 (PO 4 ) 2 (OH) 4 ·2H 2 O, was investigated by single-crystal neutron diffraction (data collected at 20 K) and electron microprobe analysis in wavelength-dispersive mode. The empirical formula of the sample used in this study is: (Na 0.91 Ca 0.01 ) Σ=0.92 (Al 2.97 Fe 3+ 0.05 Ti 0.01 ) Σ=3.03 (P 2.10 O 8 )(OH) 4 •1.74H 2 O. The neutron diffraction data confirm that the crystal structure wardite can be described with a tetragonal symmetry (spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…As a matter of fact, in fluorowardite (ideally NaAl 3 (PO 4 ) 2 (OH) 2 F 2 •2H 2 O), one of the two independent hydroxyl groups is replaced by fluorine, but the H 2 O content and configuration are virtually identical to that of wardite: the replacement OH − → F − does not generate any significant rearrangement of the structure because of the weak H-bonds of the hydroxyl groups. The H-bonding network reported by Gatta et al [4] for wardite is compatible with the previous experimental findings based on vibrational spectroscopies (e.g., [5][6][7]).…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…As a matter of fact, in fluorowardite (ideally NaAl 3 (PO 4 ) 2 (OH) 2 F 2 •2H 2 O), one of the two independent hydroxyl groups is replaced by fluorine, but the H 2 O content and configuration are virtually identical to that of wardite: the replacement OH − → F − does not generate any significant rearrangement of the structure because of the weak H-bonds of the hydroxyl groups. The H-bonding network reported by Gatta et al [4] for wardite is compatible with the previous experimental findings based on vibrational spectroscopies (e.g., [5][6][7]).…”
Section: Introductionsupporting
confidence: 91%
“…The structure of wardite contains hydroxyl groups and H 2 O molecules. Gatta et al [4] reported that whereas the unique H 2 O molecule (i.e., H1-O6-H2) experiences two strong H-bonds, as corroborated by the bonding geometry (i.e., O6-H1 . .…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations